Positioning Airlangga Hartarto dalam Gaya Komunikasi Politik Silent Authority - Iswahyu Pranawukir; Alfan Bachtiar; Agus Hitopa Sukma; Alamsyah Alamsyah; Misnan Misnan (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Silent authority is a communication style that shows a calm, polite, solution and inclusive attitude, which has been demonstrated by Airlangga Hartarto, General Chair of the Golkar Party and Coordinating Minister for Economic Affairs, a potential figure to run as a presidential/vice presidential candidate in the 2024 presidential election. This research aims to to analyze the silent authority's political communication style as a differentiation for Airlangga Hartarto ahead of the 2024 presidential election. The method used is a case study with a qualitative approach, using secondary data in the form of news, articles, interviews and public opinion surveys related to the research topic. The research results show that Airlangga Hartarto's silent authority political communication style has several characteristics, namely: (1) avoiding conflict and political polarization; (2) building open and equal communication with parties and community groups; (3) displaying performance and achievements as a form of responsibility and commitment; (4) offering concrete and realistic solutions to overcome the nation's problems; and (5) prioritizing national interests above party or personal interests. The impacts of this silent authority political communication style include: (1) increasing a positive image and public trust; (2) expanding networks and political support base; (3) strengthening his bargaining position and credibility as party leader; and (4) demonstrate capability and readiness as a future leader.